Great artists of the Italian Renaissance - Kloss, William; Teaching Company (Chantilly, VA : The Teaching Company, 2004)
Course of 36 lectures introduces the art of the Italian Renaissance.
Pt. 1. Italy and the Renaissance -- From Gothic to Renaissance -- Brunelleschi and Ghiberti in Florence -- Donatello and Luca della Robbia -- Masaccio -- Massaccio: the Branacci Chapel -- Fra Angelico and Fra Filippo Lippi -- Three specialists -- Donatello and Padua -- Piero della Francesca: individual works -- Piero della Francesca: Legend of the True Cross -- Pageant of life in Renaissance Florence -- Pt. 2. The heroic nude -- Sculpture small and large -- Botticelli: spirituality and sensuality -- Botticelli and the trouble in Italy -- Filippino Lippi -- Leonardo da Vinci: portraits and altarpieces -- Leonardo da Vinci: The Last Supper -- Michelangelo: Florentine works -- Michelangelo: Roman projects -- Michelangelo: The Sistine Chapel ceiling -- Ralphael: Madonnas and portraits -- Raphael: history paintings -- Urbino: microcosm of Renaissance civilization -- Andrea Mantegna in Padua and Mantua -- Venice: Byzantine, Gothic, and Renaissance -- Celebrating the living city -- Giovanni Bellini: the early years -- Antonello da Messina and Giovanni Bellini -- Giovanni Bellini: the late years -- Giorgione -- Giorgione or Titian? -- Titian: the early years -- A culture in crisis -- The Renaissance reformed.
Keywords: Art, Renaissance -- Italy